DEVELOPING STUDENTS’ WORKBOOK FOR SPEAKING SKILL BASED ON INQUIRY-BASED LEARNING FOR GRADE SEVEN OF SMP SWASTA ISLAM TERPADU HIKMATUL FADHILLAH MEDAN - Syafrida Matondang; Indra Hartoyo; Ade Aini Nuran (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study aims to (1) investigate how the workbook for grade seven of SMP Swasta Islam Terpadu Hikmatul Fadhillah Medan, (2) know relevant workbook needed for grade seven of SMP Swasta Islam Terpadu Hikmatul Fadhillah Medan, (3) develop a students’ workbook for speaking skill based on Inquiry-based Learning for grade seven of SMP Swasta Islam Terpadu Hikmatul Fadhillah Medan. The research was conducted by using the Research and Development method from Gall, Gall and Borg (2003). The research subject was English teacher and students for grade seven of SMP Swasta Islam Terpadu Hikmatul Fadhillah Medan. The instrument used was teacher’s interview and students’ questionnaire. The workbook was validated by validators that consist of material expert and English teacher practitioner by using questionnaires validation sheets. The data were collected by using descriptive analysis. The results of the study show that: (1) the existing workbook does not support students to do work actively, (2) relevant workbook that is needed by students is workbook based on inquiry-based learning, and (3) the developed inquiry-based learning workbook has been valid with a percentage of 95.55 % from English lecturer and 97.03% from the English teacher and this workbook is appropriate with students’ needs for speaking skills.                                                                                                 Key words: Inquiry-based Learning, Speaking, Students’ Workbook.